Pressures, green supply chain management practices and performance of ISO 14001 certified manufacturers in Malaysia - Abd Rahman, Azmawani; Ho, Jo Ann; Rusli, Khairul Anuar (Faculty of Economics and Management, Universiti Putra Malaysia, 2014)
As the language of environmentalism become more vocal globally— including in Malaysia—a growing number of organizations are intending to adopt green approaches throughout their entire supply chains. Issues of environmental protection are central and dynamic; as such, there is an ongoing need for studies to fully understand and update knowledge in this area. This paper investigates green supply chain management (GSCM) among 112 ISO14001 certified manufacturers in Malaysia. Specifically, the objectives of this study are to examine the influence of various pressures (regulation, marketing, competition, management, and cost) on the level of green practices, and the interrelationships between drivers, practices, and performance. The study also looks at the moderating effect of partner relationships. Results indicate that manufacturers in Malaysia experience high external pressures such as regulatory and marketing/customers pressures. The GSCM implementation, especially on external activities, are still at a moderate level except for internal environmental initiatives. GSCM practices affect firms’ financial/market performance and customer satisfaction, but are not significant to environmental performances. The partner relationship (trust and commitment) moderate the relationship between GSCM practices and environmental performances but is not applicable to relationships between GSCM practices and other firms’ performances such as market/financial outcomes and customer satisfaction. Subsequent implications for both theory and practice are discussed in the paper.